1997
DOI: 10.1023/a:1005760013810
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of bcl-2 gene expression in human breast cancer tissues

Abstract: The expression of estrogen receptor (ER) and bcl-2 (Bcl-2), an apoptosis protective oncogene, in normal and cancerous breast duct epithelia was immunohistochemically examined in fresh frozen tumor tissues from 142 Japanese breast cancer patients. The clinico-pathological characteristics and the disease free survival of the patients were analyzed. The expression of both the proteins was also observed in intraductal components of breast cancer. Although less than 1% of normal duct epithelia expressed ER, Bcl-2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 13 publications
5
30
0
2
Order By: Relevance
“…Noninvasive or early-stage (mostly ER-positive) breast cancer cells usually have high Bcl-2 expression, while invasive or metastatic (mostly ER-negative) breast cancers often have lower expression of Bcl-2 protein. 45,46 In the present study, the lack of Bcl-2 suppression implicated that the apoptosis of MDA-MB-231 cells induced by the CV extract was probably mediated via a Bcl-2-independent pathway (Fig. 3B).…”
Section: Discussionmentioning
confidence: 47%
“…Noninvasive or early-stage (mostly ER-positive) breast cancer cells usually have high Bcl-2 expression, while invasive or metastatic (mostly ER-negative) breast cancers often have lower expression of Bcl-2 protein. 45,46 In the present study, the lack of Bcl-2 suppression implicated that the apoptosis of MDA-MB-231 cells induced by the CV extract was probably mediated via a Bcl-2-independent pathway (Fig. 3B).…”
Section: Discussionmentioning
confidence: 47%
“…Being a potential oncogene, at least in hematopoetic tumors (where its expression is correlated with poor prognosis) Bcl-2-overexpression positively correlates with favorable clinical outcome in breast, ovarian and some other solid cancers. [5][6][7][8][9][10][11][12][13][14][22][23] It is noteworthy that even in the hematopoetic tumors Bcl-2 expression had no influence on overall survival but was rather associated with rapid tumor growth and reduced therapeutic response. 24 The existing explanation of Bcl-2 associated favorable prognosis based on the observation of a decreased proliferation of Bcl-2-overexpressing cells 7 was not confirmed by our data, although there was no difference in growth rates of the cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports indicating that these two genetic alterations have opposite prognostic values in some types of cancer: while the inactivation of p53 is associated with rapid progression and considered a negative prognostic factor, [5][6][7]9 the expression of Bcl-2 was often found to be associated with favorable prognosis in breast, ovarian and some other solid cancers. [5][6][7][8][9][10][11][12][13][14] Thus, Bcl-2 expression in breast cancer positively correlates with estrogen receptor expression, normal ploidy, higher histological tumor grade and absence of metastases, 5,6,14 suggesting that Bcl-2 in tumors somehow delays tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they all lack PR expression (Lykkesfeldt et al, 1994(Lykkesfeldt et al, , 1995. Several clinical studies have shown that the Bcl-2 expression in breast tumours is strongly correlated to both ERα and PR expression, and Bcl-2 expression is an indicator of a favourable outcome following endocrine treatment (Gee et al, 1994;Lipponen et al, 1995;Silvestrini et al, 1996;Elledge et al, 1997;Keen et al, 1997;Kobayashi et al, 1997;Olopade et al, 1997;Holmqvist et al, 1999). The decreased Bcl-2 expression associated with decreased ERα expression, and lack of response to antioestrogens observed in the resistant cell lines is in concert with the above-mentioned clinical studies.…”
Section: Discussionmentioning
confidence: 99%